2013
DOI: 10.1590/s0102-05362013000300010
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de massa seca e nutrientes pelo tomateiro 'SM-16' cultivado em solo com diferentes coberturas

Abstract: Dry mass and nutrients accumulation by tomato 'SM-16' cultivated in different mulchingThe dry mass and nutrients accumulation by tomato 'SM-16' cultivated in different mulching was carried out on an experiment in WG Fruticultura, Baraúna, Rio Grande do Norte state, Brazil, from September 2009 to January 2010. The treatments consisted of 1) uncovered soil, 2) black polyethylene film, 3) white polyethylene film, 4) gray polyethylene film and 5) black polypropylene (TNT). Treatments were arranged in split plots w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
1
4
0
3
Order By: Relevance
“…Nevertheless, the varieties did not differ in LAI, total plant DM production or proportional DM partitioning for fruits. The fruits accounted for 58-64% of DM produced by the shoot, coinciding with the results previously obtained for other beefsteak tomato varieties Aguirre et al, 2012;Lucena et al, 2013;Soares et al, 2013). The fruits can be considered as the most powerful photoassimilate sink.…”
Section: Resultssupporting
confidence: 88%
“…Nevertheless, the varieties did not differ in LAI, total plant DM production or proportional DM partitioning for fruits. The fruits accounted for 58-64% of DM produced by the shoot, coinciding with the results previously obtained for other beefsteak tomato varieties Aguirre et al, 2012;Lucena et al, 2013;Soares et al, 2013). The fruits can be considered as the most powerful photoassimilate sink.…”
Section: Resultssupporting
confidence: 88%
“…Plant dry matter accumulation was slow to 49 days, expanding later for all cultivars. The initial slow growth is due to the great spend of energy for fixation in the ground, where the roots are the preferred drain of photoassimilates (LUCENA et al, 2013). The estim ated maximum uptake for Growing Season I was 104.27 g plant -1 (CNPA G2), obtained at 93 DAS; 145.66 (CNPA G3) and 145.81 g plant -1 (CNPA G4), both at 105 DAS ( Figure 1A, 1C and 1E).…”
Section: Resultsmentioning
confidence: 94%
“…Such information is important, especially for short-cycle crops and intensive fertilisation, as for the tomato (Omaña and Peña, 2015). Pioneer studies in Brazil by Gargantini and Blanco (1963), Fernandes et al (1975), and Haag et al (1978); subsequent studies by Fayad et al (2002), Rodrigues et al (2002), Prado et al (2011, and Lucena et al (2013); and a more recent study by Purquerio et al (2016) have all reported differences in the quantities of nutrients absorbed and in yield. Such differences can be due to the genotypic variations of each cultivar, including its typology, to variations in growing conditions, and mainly to mass production (Haag and Minami, 1988).…”
Section: Introductionmentioning
confidence: 95%